Competing visions of financial inclusion in Kenya: The rift revealed by mobile money transfer - Susan Johnson (University of Bath, Centre for Development Studies (CDS), 2014)
Financial inclusion policy has been ignited globally by the rise of money transfer services over mobile telecommunications platforms. Explanations for the success of the leading example in Kenya have focussed on conditions of supply side development and the demand for domestic urban to rural remittances. This paper investigates this phenomenon by examining the financial practices of low income people and in particular the social relational dimensions of debt that underlie these mobile money transactions. By contrasting the social relations involved in mobile money to those of informal groups and banks which are the next most used services, this evidence highlights a 'fiduciary culture' in which relationships of equality and 'negotiability' dominate and which are seamlessly facilitated by mobile money in contrast to relations with banks which tend towards relations of hierarchy. I argue that this reveals a competing emic vision that questions policy makers expectations that mobile money transfer will itself seamlessly facilitate engagement with the formal sector for savings and credit.
Keywords: 330; microfinance; mobile money; financial inclusion; financial practices; Kenya; Africa